A guide to the Reservoirs Act 1975. (Institution of Civil Engineers, 2014)
'A Guide to the Reservoirs Act 1975' provides expert guidance on the application of the Reservoirs Act 1975, reflecting the current views and practices of the dam engineering profession. This fully updated second edition for reservoirs located in England incorporates the latest amendments introduced through the Flood and Water Management Act 2010, reflecting a more risk-based approach to reservoir regulation. The new edition also incorporates updates from the Water Act 2003.